The Regulatory Domain of Human Tryptophan Hydroxylase 1 Forms a Stable Dimer - Zhang, Shengnan (Biochem Biophys Res Commun, 2016)
The three eukaryotic aromatic amino acid hydroxylases phenylalanine hydroxylase, tyrosine hydroxylase, and tryptophan hydroxylase have essentially identical catalytic domains and discrete regulatory domains. The regulatory domains of phenylalanine hydroxylase form ACT domain dimers when phenylalanine is bound to an allosteric site. In contrast the regulatory domains of tyrosine hydroxylase form a stable ACT dimer that does not bind the amino acid substrate. The regulatory domain of isoform 1 of human tryptophan hydroxylase was expressed and purified; mutagenesis of Cys64 was required to prevent formation of disulfide-linked dimers. The resulting protein behaved as a dimer upon gel filtration and in analytical ultracentrifugation. The s(w) value of the protein was unchanged from 2.7–35 µM, a concentration range over which the regulatory domain of phenylalanine hydroxylase forms both monomers and dimers, consistent with the regulatory domain of tryptophan hydroxylase 1 forming a stable dimer stable that does not undergo a monomer-dimer equilibrium. Addition of phenylalanine, a good substrate for the enzyme, had no effect on the s(w) value, consistent with there being no allosteric site for the amino acid substrate.